The Relationship between the Use of the Ibis Paint X Application and the Motivation to Learn Fashion Design in Grade XI Students of Fashion Design at SMK Negeri 1 Salatiga - Nur Rizki Amalia; Muh Fakhrihun Na'am (Jurnal Penelitian Pendidikan, 2026)
This study aims to examine the relationship between the use of the Ibis Paint X application and the motivation to learn to design fashion at SMK Negeri 1 Salatiga. This research is a quantitative approach research with a correlational design. The population in this study is all students of class XI fashion at SMK Negeri 1 Salatiga which totals 71 students, and the sample in this study uses total sampling, The sampling technique uses total sampling, namely making the population as a sample, there is a total sampling because the population is less than 100. The data collection technique used a Likert scale questionnaire. The data in this study were analyzed using descriptive and inferential statistics. Hypothesis test using Pearson correlation. The results of the study obtained that there was a significant relationship between the use of the Ibis Paint X application and the motivation to learn to design the fashion of grade XI students, the fashion show had a pearson correlation coefficient value of 0.559 and a significance value (sig. 2-tailed) of 0.000. This shows that there is a relationship between the use of the Ibis Paint X application and the motivation to learn to design fashion in grade XI students of fashion at SMK Negeri 1 Salatiga with the correlation category being.